2014
DOI: 10.4172/2157-7471.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Root-rot and Stem-canker Control in Faba Bean Plants by Using Some Biofertilizers Agents

Abstract: Some biofertilizers agents i.e. Rhizobium leguminosarum var. fabae, Bacillus megaterium var., phosphaticum and Trichoderma harizianum play important roles in enhancing the plant growth and controlling several diseases i. e. root rot and stem canker disease. In this work, under greenhouse conditions, Rhizoctonia solani caused dampingoff and death of all faba bean seedlings, however the three tested microorganisms resulted good biocontol role against the pathogenic fungus and the application of T. harizianum gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…pod fresh and dry weights, seed number, seed weight and ash pod weight. These results are agreement with those obtained by Farfour and Al-Saman (2014). They suggested that application of T. harzianum enhanced the plant growth of faba bean and controlled root rot disease caused by R. solani in greenhouses.…”
Section: Discussionsupporting
confidence: 92%
“…pod fresh and dry weights, seed number, seed weight and ash pod weight. These results are agreement with those obtained by Farfour and Al-Saman (2014). They suggested that application of T. harzianum enhanced the plant growth of faba bean and controlled root rot disease caused by R. solani in greenhouses.…”
Section: Discussionsupporting
confidence: 92%
“…Faba bean seeds Giza 3 were inoculated with R. leguminosarum at the rate of 10 g / kg -1 seed before planting by immersing them in a sugar solution at a concentration of 20% where it was used as an adhesive substance. The treated seeds of peat pollen were coated with 16% gum arabic as an adhesive agent and left for 30 minutes in the shade Until completely dry according to Farfour and Al-Saman, (2014). Six faba bean seeds were planted in each pot, and five pots were identified as duplicates for each transaction in a completely random template design.…”
Section: Laboratory Tests: Effect Of the Two Organic Fungicides Elemental Sulfur And Copper Oxychloride On The Linear Growth Of The Pathomentioning
confidence: 99%
“…The inoculation of legumes with rhizobia and the effect of this on the growth of these crops have been known for a long time since it has been used to a large extent in agriculture to improve crops due to its ability to fix nitrogen (Chen et al, 2018). Rhizobium symbiosis with legumes produces 50% of 175 million tons of total biological N2 fixation annually worldwide (Roughley, et al, 1983;Shaban and Bramawy, 2011;Farfour andAl-Saman, 2014, Yadav andVerma, 2014;Ouma et al, 2016;Chen et al, 2018). Rhizobia can also serve as biological control agents of some plant pathogens in legume and non-legume plants (Antoun and Prévost, 2005;Kumawat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%